PENERAPAN PASAL 112 DAN PASAL 127 UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Nugroho, Bastianto; Sumarso, Sumarso; Yustianti, Surti; Roesli, Mohammad (Program Pascasarjana Universitas Sunan Giri Surabaya, 2019)
Narcotics are required by humans for treatment to meet the needs in the field of medicine, and scientific studies required a continuous narcotic production for the sufferers. Based on the Act No. 35 year 2009 about narcotics is mentioned that drugs on one side is a drug or ingredient that is beneficial in the field of medicine or health care and development of science and on the other hand can also cause a dependency that is very harmful when abused or used without strict control and supervision. Narcotics, when used irregular according to dosage/dose, will be a physical and mental danger for those who use it and can cause dependence on the user itself. It means a powerful psychological desire to use the drug continuously due to emotional causes. Law Number 35, the year 2009, about narcotics governs the entire narcotics criminal act in Indonesia. Law Number 35, the year 2009, about drugs is also expected to provide a deterrent effect for dealers or narcotics addicts. But in Law No. 35 year 2009 About narcotics categorizes narcotic criminal acts in Indonesia into distributors, carriers, and addicts.